Notes on the Melitaea ornata Christoph, 1893, complex in the Levant (Lepidoptera: Nymphalidae) including new synonymy and observations on lectotype designations for Melitaea phoebe dorae Graves, 1925 - Russell, Peter J. C.; Tennent, W. John (Zootaxa, 2023)
Two independent designations for a lectotype of Melitaea phoebe dorae Graves, 1925, are discussed and resolved. Errors of labelling in presentation of some Melitaea taxa in recent literature are identified. Synonymy of the name klili Benyamini, 2021, with M. telona Fruhstorfer, 1908, is confirmed; the name tzinensis Benyamini, 2023 syn nov., is discussed and placed in synonymy with M. telona Fruhstorfer, 1908.